2022
DOI: 10.3934/dcds.2022072
|View full text |Cite
|
Sign up to set email alerts
|

Topological characterizations of Morse-Smale flows on surfaces and generic non-Morse-Smale flows

Abstract: <p style='text-indent:20px;'>It is known that <inline-formula><tex-math id="M1">\begin{document}$ C^r $\end{document}</tex-math></inline-formula> Morse-Smale vector fields form an open dense subset in the space of vector fields on orientable closed surfaces and are structurally stable for any <inline-formula><tex-math id="M2">\begin{document}$ r \in \mathbb{Z}_{\geq 1} $\end{document}</tex-math></inline-formula>. In particular, <inline-formula><tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Lemma 3.3 and Lemma 3.4 imply Theorem 3.1. Notice that the similar statement holds for quasi-regular Morse-Smale-like flows under the non-existence of fake limit cycles because quasi-regular Morse-Smale-like flows are quasi-Morse-Smale (i.e the resulting flows obtained from quasi-regular gradient flows by replacing singular points with limit cycles and pasting limit cycles) (see [6] for definition details). We will state the statement in the second from the last section more precisely.…”
Section: Combinatrial Structure Of the Space Of Gradient Flowsmentioning
confidence: 72%
See 3 more Smart Citations
“…Lemma 3.3 and Lemma 3.4 imply Theorem 3.1. Notice that the similar statement holds for quasi-regular Morse-Smale-like flows under the non-existence of fake limit cycles because quasi-regular Morse-Smale-like flows are quasi-Morse-Smale (i.e the resulting flows obtained from quasi-regular gradient flows by replacing singular points with limit cycles and pasting limit cycles) (see [6] for definition details). We will state the statement in the second from the last section more precisely.…”
Section: Combinatrial Structure Of the Space Of Gradient Flowsmentioning
confidence: 72%
“…(2) There are at most finitely many limit cycles. In [6,Theorem B], it is shown that a flow on a compact surface is a gradient flow with finitely many singular points if and only if the flow is Morse-Smale-like without elliptic sectors or non-trivial circuits.…”
Section: 24mentioning
confidence: 99%
See 2 more Smart Citations